Diagenesis of the oolite group between Blaen Onneu and Pwll Du, lower carboniferous, South Wales - Raven, Madeleine Julia (1983)
The diagenetic history of the Oolite Group from Pwll du to Blaen Onneu has been unravelled. Cement types, solution events, dolomitisation, concretions and other authigenic minerals are described.